2015
DOI: 10.1590/abd1806-4841.20153252
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic profile of chromoblastomycosis in a referral service in the midwest of São Paulo state (Brazil)

Abstract: Chromoblastomycosis is one of the most frequent deep mycoses found in rural populations. This cross-sectional, retrospective and descriptive study was conducted with cases of chromoblastomycosis diagnosed throughout 20 years. A higher prevalence was observed among White male rural workers, with an average age of 59.69 years. Median time between onset of symptoms and diagnosis was 156 months. Lesions were predominantly located on the lower limbs; 34% of cases reported previous trauma. The most common associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 9 publications
4
19
0
2
Order By: Relevance
“…In all series reviewed, F. pedrosoi and C. carrionii were the most common . Chromoblastomycosis is primarily of the tropics and subtropics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all series reviewed, F. pedrosoi and C. carrionii were the most common . Chromoblastomycosis is primarily of the tropics and subtropics.…”
Section: Discussionmentioning
confidence: 99%
“…Ten isolates were identified by phenotypic and molecular analysis and demonstrated that nine isolates from Mexico and Venezuela were 100% homologous and one showed a small genetic distance . In a Brazilian series, the average age of 59.69 years, and a median time between onset of symptoms and diagnosis was 156 months …”
Section: Discussionmentioning
confidence: 99%
“…En Perú sólo se han reportado entre 10 a 49 casos, número similar a lo descrito en Argentina y E.U.A; pero menos que en Venezuela y México. Sin embargo, es en Brasil donde se ha comunicado el mayor número de casos (500 publicados) 9 , con una prevalencia estimada de uno de cada 196.000 habitantes 10 . La presentación clínica de ambos casos fue en las extremidades superiores, en contraste con un estudio realizado en Brasil, donde la presentación más frecuente fue en los miembros inferiores (81,5%) 7 .…”
Section: Discussionunclassified
“…Para ello se debe prestar mucha atención en la recolección, debiendo realizarse de lesiones cutáneas cubiertas de puntos negros. La muestra deberá evaluarse mediante examen microscópico directo con hidróxido de potasio al 20% 4 , una técnica sencilla, económica y ampliamente utilizada como tamizaje 10 . El cultivo micológico como estándar de oro, es confirmatorio y permite estudiar a la especie fúngica tanto en la macroscopia como en microscopia.…”
Section: Discussionunclassified
“…After inoculation, the disease progresses slowly and spontaneous resolution is not observed unless treated. 87,88 In general, the disease remains localized to the area of the initial infection or neighboring skin, but lymphatic and hematogenous dissemination may occur, causing metastatic lesions. Annular lesion resolves centrally with scarring.…”
Section: Accepted Manuscriptmentioning
confidence: 99%